Characterization of Hedgehog Acyltransferase Inhibitors Identifies a Small Molecule Probe for Hedgehog Signaling by Cancer Cells - Rodgers, Ursula R. (ACS Chem Biol, 2016)
[Image: see text] The Sonic Hedgehog (Shh) signaling pathway plays a critical role during embryonic development and cancer progression. N-terminal palmitoylation of Shh by Hedgehog acyltransferase (Hhat) is essential for efficient signaling, raising interest in Hhat as a novel drug target. A recently identified series of dihydrothienopyridines has been proposed to function via this mode of action; however, the lead compound in this series (RUSKI-43) was subsequently shown to possess cytotoxic activity unrelated to canonical Shh signaling. To identify a selective chemical probe for cellular studies, we profiled three RUSKI compounds in orthogonal cell-based assays. We found that RUSKI-43 exhibits off-target cytotoxicity, masking its effect on Hhat-dependent signaling, hence results obtained with this compound in cells should be treated with caution. In contrast, RUSKI-201 showed no off-target cytotoxicity, and quantitative whole-proteome palmitoylation profiling with a bioorthogonal alkyne-palmitate reporter demonstrated specific inhibition of Hhat in cells. RUSKI-201 is the first selective Hhat chemical probe in cells and should be used in future studies of Hhat catalytic function.